Measuring academic satisfaction in nursing students: a systematic review of the instruments - Rossini Silvia; Mazzotta Rocco; Kangasniemi Mari; Badolamenti Sondra; Macale Loreana; Sili Alessandro; Vellone Ercole; Alvaro Rosaria; Bulfone Giampiera (De Gruyter, 2025)
Student academic satisfaction is one of the most important factors affecting the success and quality of a higher education institute and is an indicator about teaching and learning. This study aims to summarize and critically evaluate the instruments assessing academic satisfaction in nursing education. A systematic review was undertaken, PRISMA were used for the screening of studies. MEDLINE, Cochrane, Scopus and CINAHL were searched using MeSH terms; seven eligible articles were identified referring to five assessment tools. COSMIN was used for evaluation of the methodological of the instruments. The systematic review identified five satisfaction measurement tools used in nursing education. The analysis of the instruments rarely considered a confirmative validity structure, measurement error or criterion validity. The best available instrument was the Nursing Students Satisfaction Scale (NSSS) for validation methodology; however, it needs further validation studies that consider CFA, reliability, criteria validity, hypothesis testing and measurement error.